SYSTEMATIC METHODOLOGY "EMU" UNIVERSITY MERCADOLÓGICO GEAR - Pilco, Wilian (2017)
Universities and public polytechnic schools for its operation and validity are evaluated and accredited based on a set of criteria, indicators and sub-criteria of quality that are part of an objective assessment, but in its complement it is necessary to apply a subjective evaluation to determine the levels Satisfaction of the users served, and based on their results design university marketing strategies. The methodological scaffolding was based on a quantitative approach applied research, a problematic - hypothetical scientific characterization, we worked the inductive - deductive, analytical, synthetic and systemic methods; A non-experimental and cross-sectional design with a correlational investigative level. The result obtained is a systematic methodology called "EMU", to evaluate the institutional image and propose university marketing strategies that allow the strengthening and positioning of the educational quality and the sustainable and sustainable development of the public university in favor of Ecuadorian society.